Dialect phonemes incorporated into the standard Kadazandusun language - Henry Bating; Loi Chek Kim; Siti Aishah Ramli (International Journal of Languages, Literature and Linguistics, 2018)
The present study is an analysis of vocoid and contoid variation in Kadazandusun dialects and it has animplication for the teaching of standardized spelling and pronunciation of the Kadazandusun language in Malaysia. The study aims to analyze the phonemes of the Kadazandusun dialects in order to determine the phonemes and graphemes that have been incorporated into the standard Kadazandusun language. This paper uses the qualitative descriptive method of literature study. The sample comprises 10 dialects, namely (Tambunan), Murut Timugon, Murut Tagol, Tombonuo and Kolobuan. These dialects were selected from the three language families in Sabah, namely Dusunic, Murutic and Paitanic. A -dialectal analysis was performed on the segmental phonemic description and phonemes of each dialect to find common equation similarities that have provided a base for standardizing the phonemes and graphemes of the Kadazandusun language. The findings show that the Kadazandusun language has 36 phonemes comprising six vocals, seven diphthongs and 23 consonants. All the 36 phonemes are represented by 21 graphemes of Romanized letters. Other phonemes are denoted by diacritical signs and two vowel arrangements